Altered Microcirculatory Blood Flow is Associated with Delayed Liver Regeneration in TLR4-mutant Mice - M. Marlini; A. Mabuchi; B. Mallard; M.N. Hairulhisyam; A. Wheatley (Springer, 2024)
Background and aims: Haemodynamic events and the changes to hepatic blood flow are the least studied and least understood aspects in liver regeneration. It has been previously reported that liver regeneration is delayed in C3H/HeJ mice, a mouse that is hyporesponsive to lipopolysaccharide (LPS), due to a point mutation in trl4 gene. Using IVFM, we aimed to determine whether delayed liver regeneration in these TLR4-mutant mice was associated with altered hepatic microcirculation during liver regeneration.